Some Aspects of the Poetic Technique of Vedic Kavis: Do the compositional structures and lexical or phonetic features of Vedic Hymns reveal complementary information on their content? - Ježić, Mislav (Array, 2014)
Although the Rgvedic hymns represent the oldest collection of poetry preserved in India, and one of the oldest literary monuments in the Indo-European languages, the poetical technique of their poets is neither simple nor primitive. It implies different metres appropriately used in poems, and stylistic figures such as comparison, metaphor, hyperbole and paradox, as well as compositional devices such as chiasmus, parallelism, etc. These stylistic figures often imitate the components of the structure of the subject referred to in the poem. Very often the basic coherent unit of a hymn is a stanza, and the link between different stanzas can be loose. However, different stanzas are sometimes connected by an underlying structure that provides a kind of unity to the whole hymn or to its constituent parts. In this paper, compositional devices, anagrams (actually cryptophonic expressions in oral literature), inversion of relations between the gods, or the covert provision and solution of a riddle, largely unnoticed by scholars until now, are illustrated and analysed as compositional stratagems on the example of some hymns. Of course, all of these means are not used uniformly by all of the kavis in all of the books, and in the future these poetic procedures might help us distinguish different periods and different poets in the Rgvedic corpus in even greater detail. These procedures do not only demonstrate the formal ingenuity of the poets, but also contribute to the construction of the deeper meaning of the poem.